2008
DOI: 10.1080/09286580802077716
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations of HIV Infections in India in the Era of HAART: Analysis of 100 Consecutive Patients Evaluated at a Tertiary Eye Care Center in India

Abstract: CMV Retinitis (20%) (20/100) is still the most common manifestation of HIV infection in this series, even in the era of HAART, and is more common than HIV vasculopathy. Immune recovery uveitis is appears to be more common with the introduction of HAART in absence of affordable anti CMV therapy in India. 7% (7/100) of patients present with ophthalmological features as the initial manifestation of HIV. As before, most (70%) (28/40) of the ophthalmic manifestations of HIV infection are present when CD4 count is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 38 publications
9
53
4
Order By: Relevance
“…The most common ophthalmic manifestations associated with HIV infection in India have been reported to be HIV retinopathy, cytomegalovirus retinitis (20%), and opportunistic infections. [20][21][22][23][24] Sudharshan et al 25 reported 4 cases of OSSN as part of their study of anterior segment manifestations in HIV. However, to the best of our knowledge, no study has reported the prevalence of HIV in OSSN in India.…”
Section: Discussionmentioning
confidence: 99%
“…The most common ophthalmic manifestations associated with HIV infection in India have been reported to be HIV retinopathy, cytomegalovirus retinitis (20%), and opportunistic infections. [20][21][22][23][24] Sudharshan et al 25 reported 4 cases of OSSN as part of their study of anterior segment manifestations in HIV. However, to the best of our knowledge, no study has reported the prevalence of HIV in OSSN in India.…”
Section: Discussionmentioning
confidence: 99%
“…3,59 In earlier studies, CMV retinitis and HIV retinopathy seemed to be less prevalent in India than in western countries, reported between 17% and 20% and between 7% and 15%, respectively. 8,60,61 However, more recent data from a study of 1286 patients with AIDS are more consistent with other parts of the world. 62 Of patients not receiving HAART, CMV retinitis was diagnosed in 39%, HIV retinopathy in 22%, HZO in 7%, and ocular tuberculosis in 0.5%.…”
Section: Sub-saharan Africamentioning
confidence: 80%
“…Contrary to this, a study done by Sujit Gharai et al consisted of 100 consecutive HIV cases, of whom only 17% had category A, 23% had category B, and the majority (60%) had category C HIV infection. 7 The ophthalmic manifestations in their study in decreasing order of frequency were CMV retinitis (20%), neuro-ophthalmic manifestations (12%), complicated cataract (6%), IRU in (5%), acute retinal necrosis (3%), choroiditis (2%), keratouveitis (1%), and corneal ulcer (1 %). Only 68% of these patients were on ART as compared to 85.05% cases in our study.…”
Section: Discussionmentioning
confidence: 95%